Implementation of ARIMA for Prediction of Paddy Rice Production in Cisolok Sub-District, Sukabumi District - Mugni, Rafi Abdul; Setiawan, Iwan Rizal; Indrayana, Didik (Indonesian Scientific Journal, 2025)
Indonesia as an agricultural country, agriculture, especially paddy production, plays an important role in food security. However, Cisolok District, Sukabumi Regency faces challenges in terms of effective rice production management. This study aims to improve the accuracy of rice production prediction in Cisolok District by implementing Arima. The methodology used is Knowledge Discovery in Databases (KDD), which includes data selection, data pre-processing, model selection, model training, and model evaluation. The data used include weather attributes and paddy production, which are collected from various related sources. The results of the study indicate that the model built with Arima provides accurate estimates and can help farmers and decision makers in planning and managing paddy production more efficiently. These findings are expected to increase paddy productivity in Cisolok District, Sukabumi Regency.